Characteristics of Endometriosis Patients at Sultan Agung Hospital Semarang During the Period 2018 - 2019 - Aryani, Rini; Ashari, Muslich (Universitas Ahmad Dahlan, 2023)
Endometriosis is a female gynecological disorder that is defined as the presence of ectopic growth of endometrial glands and stroma (outside the uterine cavity). Infertility, chronic pelvic pain, and dysmenorrhea caused by endometriosis greatly impact the quality of life and productivity of women of reproductive age (18- 45 years). The aim of this study was to describe the characteristics of risk factors for endometriosis sufferers at RSI Sultan Agung Semarang during the period 1 July 2018 to 31 July 2019. This study used a retrospective descriptive study, using medical record data of endometriosis sufferers at Sultan Agung Hospital in Semarang. The time allocation for this research was August - October 2019. Data analysis was carried out univariately on each variable from the results of this research to see the frequency and percentage distribution. The research variables were age, education level, occupation, parity, age at menarche, clinical symptoms, location of endometriosis, disease stage, and management. The results of the study showed that most endometriosis patients were of reproductive age (64.8%), with the highest education level of endometriosis patients being high school (31.5%), housewife being the most dominant occupation (44.4%), and endometriosis patients are dominated by multiparas (37%), the most common marital status is married (87%), with the main symptom frequently found being dysmenorrhea (70.4%) and the most frequently given therapy is operative (25.9%). The majority of endometriosis sufferers are of reproductive age with a high school education level and housewives.